DENTAL REMAINS OF EARLY BISON FROM THE TATROT FORMATION OF THE UPPER SIWALIKS, PAKISTAN - M. A. Khan; S. Nasim; T. Ikram; A. Ghafoor; M. Akhtar (Journal of Animal and Plant Sciences, 2011)
Dental fossil remains assigned to cf. Bison sivalensis are described and discussed. The recovered assemblages comprising 3 upper molars and one lower premolar reflect the morphological features of the genus Bison. The discovered material comes from the late Pliocene continental deposits of the Tatrot village (Tatrot Formation, Upper Siwaliks, northern Pakistan) dated approximately from 3.3 to 2.6 Ma. A new finding for the site documents the dentition of the early bison.
Keywords: Vertebrates; Mammals; Bovidae; Bovini; Bison; Siwaliks.